The Persistence of Gender Stereotypes in Teaching History. A Study Through Textbooks and Perceptions of Students in Compulsory Secondary Education in Spain - Gómez-Carrasco, Cosme Jesús (2016)
The aim of this paper is to study the persistence of gender stereotypes in History Education. This study is conducted through an iconographic analysis of textbooks and the perception of students in Secondary Education in Spain. The educational reforms carried out in Spain over the last twenty five years have improved some aspects of gender equality, especially the introduction of some cross-cutting themes related to this subject. However, investigations related to sexism in school materials have revealed the persistence of some gender clichés. To do this research, we have analysed 128 pictures on three History textbooks for fourth grade students of Compulsory Secondary Education in Spain. In the analysis, various categories were combined and they allowed a multifactorial study. Furthermore, these data have been contrasted with the answers given to a questionnaire on gender stereotypes by 152 students of two grades. The results show that, despite the improvement of textbooks, an imbalance still survives in the representation of male and female genders and in the images associated with them. In the answers to the questionnaire, disparate findings are also perceived. Although some sexist prejudices seem to be overcome, especially those related to the role of men and women at home, images and negative stereotypes about gender relations and women’s role still persist.